PENGGANTIAN BIAYA KEPADA SAKSI ATAU AHLI DALAM RANGKA MEMBERIKAN KETERANGAN DALAM SISTEM PERADILAN PIDANA (Studi Penelitian di Wilayah Hukum Pengadilan Negeri Takengon) - Purba, Lisa Purba Hajini; S, Sumiadi; Y, Yusrizal (Jurnal Ilmu Hukum Reusam, 2020)
Summons of witnesses at each level of criminal case examination has consequences for the cost of attending the summons. So far, the provisions regarding the cost of summoning witnaesses and experts have been regulated in Article 229 of the Criminal Procedure Code and Law Number 13 of 2006 concerning Protection of Witnesses and Victims and Law Number 2 of 2002 concerning Procedures for Protection of Witnesses and Victims in Human rights violations, however, in reality the fees that have been regulated in the law are not fully provided to all witnesses and even if there are costs they are not up to standard and not optimal. These costs include accommodation costs, consumption costs, transportation costs and costs of reimbursing lost income due to having to attend calls. The purpose of this research is to find out and explain the compensation mechanism to witnesses or experts in order to differentiate information in the criminal justice system in the jurisdiction of the Takengon District Court and what are the obstacles in reimbursing costs to witnesses or experts in order to provide information in the criminal justice system in the region. the law of the Takengon District Court. This type of research is juridical empirical, that is, approaching the problem through legal research by looking at the prevailing legal norms and relating them to the facts that exist in society in connection with the problems encountered in the research.